Estimates of the Bernstein widths and their analogs - Kushpel, A. K. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The estimates of exact order are obtained for Bernstein widths. A new scale of widths intermediate between Kolmogorov and Bernstein ones is introduced.